Elevation of Circulating Th17/Th22 Cells Exposed to Low-Level Formaldehyde and Its Relevance to Formaldehyde-Induced Occupational Allergic Contact Dermatitis. Issue 9 (September 2017) - Mai, Weihua; Liu, Xingwei; Su, Guangxiao; Zhou, Wenying; Wen, Ziping; Lu, Dongqing
Abstract : Objectives: The aim of this study was to investigate the effects of formaldehyde exposure on Th17 and Th22 cells and its relevance to human occupational allergic contact dermatitis (OACD). Methods: Circulating IL17-/IL22-secreting cells and serum IL17/IL22 levels in formaldehyde-exposed workers at Occupational Exposure Limit and nonexposed controls were assessed. Results: The IL17 + and IL22 + cell population were detected in both CD3 + CD8 - and CD3 + CD8 + cells. The percentages of circulating IL17 + and IL22 + T cells in the workers with and without ACD history were all elevated, which were more remarkable in the ones with ACD history. Serum levels of IL17 and IL22 between the workers and controls were not significantly different. Conclusions: Low-level formaldehyde exposure may increase circulating IL17-/IL22-producing T cells (CD8 - and CD8 + ), possibly involved in the development of human OACD. But it may not alter serum levels of IL17/IL22 before the appearance of OACD symptoms.